2022
DOI: 10.5888/pcd19.220114
|View full text |Cite
|
Sign up to set email alerts
|

Differences in COVID-19 Hospitalizations by Self-Reported Race and Ethnicity in a Hospital in Honolulu, Hawaii

Abstract: Introduction The true extent of racial and ethnic disparities in COVID-19 hospitalizations may be hidden by misclassification of race and ethnicity. This study aimed to quantify this inaccuracy in a hospital’s electronic medical record (EMR) against the gold standard of self-identification and then project data onto state-level COVID-19 hospitalizations by self-identified race and ethnicity. Methods To identify misclassification of race and ethnicity in the EMRs of a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Limitations of this study include the inherent variability in collecting self-identified race and ethnicity data for entry into the EHR, with a 2022 study 6 suggesting that this approach underestimates identification of Native Hawaiian and Pacific Islander patients in COVID-19 hospitalizations. 6 Furthermore, the vaccine data are incomplete, given that patients may have received vaccines at other sites not captured in the EHR. In addition, too few uninsured patients were admitted to this hospital to evaluate for associations with race and ethnicity or vaccine status in our analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations of this study include the inherent variability in collecting self-identified race and ethnicity data for entry into the EHR, with a 2022 study 6 suggesting that this approach underestimates identification of Native Hawaiian and Pacific Islander patients in COVID-19 hospitalizations. 6 Furthermore, the vaccine data are incomplete, given that patients may have received vaccines at other sites not captured in the EHR. In addition, too few uninsured patients were admitted to this hospital to evaluate for associations with race and ethnicity or vaccine status in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 , 5 However, while disaggregation of data can be challenging, several publications early in the COVID-19 pandemic suggested markedly disparate outcomes that merit further exploration. 4 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…Seto and coauthors of the article “Differences in COVID-19 Hospitalizations by Self-Reported Race and Ethnicity in a Hospital in Honolulu, Hawaii” were selected as winners in the doctoral category ( 7 ). Pointing out that COVID-19 has exacted a tremendous toll on racial and ethnic groups in the US, they sought to identify the extent to which race and ethnicity were misclassified in COVID-19 hospitalizations.…”
Section: Winners and Submissionsmentioning
confidence: 99%
“…Over the years, PCD has refined the purpose of the student research publication opportunity to include these 5 primary goals (3): Sixteen student research papers were submitted for the contest in 2022, and all submissions underwent the same peer-review process as any other manuscript submitted to the journal for consideration. Eight of the 16 papers were successful in making it through a rigorous review process before being accepted for publication (4)(5)(6)(7)(8)(9)(10)(11). Student research papers addressed a range of topics: COVID-19 and various aspects of health, food insecurities among caregivers in southern states, the relationship between physical activity and depression among high school students, perceptions of neighborhood development on active living among community residents, use of a cancer index as a predictor of common cancers, and spatial analysis of breast cancer mortality rates in rural states.…”
Section: Goals and Submission Requirementsmentioning
confidence: 99%
See 1 more Smart Citation